Making Decisions About Long-Term Institutional Care Placement Among People With Dementia and Their Caregivers: Systematic Review of Qualitative Studies. (29th May 2019) - Teng, Claris; Loy, Clement T; Sellars, Marcus; Pond, Dimity; Latt, Mark D; Waite, Louise M; Sinka, Victoria; Logeman, Charlotte; Tong, Allison
Abstract: Background and Objectives: People with dementia become increasingly dependent on others for care as cognition declines. Decision making about placement of people with dementia into long-term institutional care can be emotionally complex. The objective of this review is to describe experiences and perspectives of people with dementia and their family caregivers in making decisions about institutional care placement. Research Design and Methods: MEDLINE, Embase, PsycINFO, and CINAHL were searched from inception to August 2018. Thematic synthesis was used to analyze results. Results: We included 42 studies involving 123 people with dementia and 705 family caregivers from 12 countries. We identified five themes: ensuring safety (avoiding injury due to frailty, protecting against dangerous behaviors, preventing aggressive encounters), reaching breaking point (insufferable burden of caregiving, needs exceeding capabilities, intensifying family conflict, loneliness and isolation, straining under additional responsibilities, making extreme personal sacrifices), vulnerability in lacking support (ill-prepared for crisis, unable to access professional expertise, unpredictable prognostic trajectory, uncertainty navigating health care services, pressured by limited placement opportunities, high cost of placement, resenting loss of autonomy), avoiding guilt of abandonment (sharing accountability, mitigating against disagreement and stigma, reluctance to relinquish caregiving, seeking approval), and seeking reassurance and validation (preserving personhood and former identity, empowerment through engagement, assurance of care quality, acceptance from other care residents). Discussion and Implications: People with dementia and family caregivers feel vulnerable, disempowered, and guilty in decision making about institutionalization. Person-centered communication and support strategies that foster confidence and reassurance are needed to assist people with dementia and caregivers to make decisions about placement into long-term institutional care settings.